Identification of a cellularly active SIRT6 allosteric activator. (December 2018) - Huang, Zhimin; Zhao, Junxing; Deng, Wei; Chen, Yingyi; Shang, Jialin; Song, Kun; Zhang, Lu; Wang, Chengxiang; Lu, Shaoyong; Yang, Xiuyan; He, Bin; Min, Jinrong; et al.
Abstract SIRT6, a member of the SIRT deacetylase family, is responsible for deacetylation of histone H3N ε -acetyl-lysines 9 (H3K9ac) and 56 (H3K56ac). As a tumor suppressor, SIRT6 has frequently been found to have low expression in various cancers. Here, we report the identification of MDL-800, a selective SIRT6 activator. MDL-800 increased the deacetylase activity of SIRT6 by up to 22-fold via binding to an allosteric site; this interaction led to a global decrease in H3K9ac and H3K56ac levels in human hepatocellular carcinoma (HCC) cells. Consequently, MDL-800 inhibited the proliferation of HCC cells via SIRT6-driven cell-cycle arrest and was effective in a tumor xenograft model. Together, these data demonstrate that pharmacological activation of SIRT6 is a potential therapeutic approach for the treatment of HCC. MDL-800 is a first-in-class small-molecule cellular SIRT6 activator that can be used to physiologically and pathologically investigate the roles of SIRT6 deacetylation. The use of an allosteric drug-design method resulted in the identification of a first-in-class cellularly active SIRT6 activator that induces cell-cycle arrest in the G0 –G1 phase, thus suppressing proliferation in human hepatocellular carcinoma cells.